Extensive study on electrocution at the Bureau of Legal Medicine of Milan (1993–2017): Determination of the current mark with scanning electron microscope/energy-dispersive X-ray analysis on paraffin-embedded samples. (June 2019) - Boracchi, Michele; Domenico Luigi Crudele, Graziano; Gentile, Guendalina; Maciocco, Francesca; Maghin, Francesca; Marchesi, Matteo; Muccino, Enrico; Zoja, Riccardo
Literature on electrocution in Italy is limited. The authors have focused their attention on the use of scanning electron microscope/energy-dispersive X-ray analysis in order to evaluate the current mark even on paraffin-embedded samples. A total of 24, 104 autopsies were performed at the Section of Legal Medicine of Milan (1993–2017); all cases of death caused by electrocution (low and high voltage) were selected. We assessed a regular histological examination, a toxicological examination and detected metallisation with energy-dispersive X-ray spectroscopy analysis on paraffin-embedded tissues of typical current marks. We collected 27 high-voltage fatalities and five cases of low-voltage suicide electrocution; the technique revealed itself as sensitive. In all cases, microscopic examination highlighted the typical signs of electric current and thermal damage but the histochemical specific stainings for copper and iron gave negative results. Scanning electron microscope/energy-dispersive X-ray analysis, assessed on these same samples, even when paraffin-embedded, however, enabled us to detect these elements and differentiate between the various metal residues involved in the electrocution process. Based on their experience, authors advise the use of scanning electron microscope/energy-dispersive X-ray analysis on electrocution deaths to provide information for forensic diagnosis.